ASSOCIATION BETWEEN SERUM FERRITIN LEVEL AND LIVER FUNCTION TESTS IN CHILDREN WITH BETA-THALASSEMIAIN THALASSEMIA CENTER OF KUT HOSPITAL - Jabbar, Hawraa Fadhil; Attafi, Fadhil J; Kadhim, Emad Jawad; Jarallah, Kareem Raheel (Journal of Medical Genetics and Clinical Biology, 2024)
Background:Thalassemia represents a heterogeneous autosomal recessive hereditary anemia.Ferritin is a 450 KDa soluble protein. It can be found in all of the body's cells, but it's particularly abundant in marrow macrophages, spleen, and liver. Objective:In patients with β thalassemia major and β thalassemia Intermedia, serum ferritin levels are measured, and their correlation with bilirubin levels, liver enzymes AST (aspartate transaminase) and ALT (alanine transaminase), in beta-thalassemia major and β thalassemia Intermedia. Patients and Methods:A cross-section study that involved 90 patientsincluded 50 Thalassemia Major (TM) and 40 Thalassemia intermediate(TI). Patients who were randomly chosen for this study would be gathered from the Kut Hospital Thalassemia Center. Every patient's are kid, aged 5 to 17, regardless of gender. Abbott C4000 Architect Additionally, the TSB, ALT, AST, and serum ferritin were determined using the Cobas c 111 analyzer. Results:The studies include both genders 52.9% of the females had B-thalassemia major and 47.1% had β-thalassemia intermediate, whereas 57.1% of the men had βTM and 42.9% had βTI. There were 37.8% of females and 62.2% of males in the sample.Patients with severe thalassemia exhibited a statistically significant increase in the mean± SD of serum ferritin (4016.54 ± 2500.81 ng/ml) compared to the mean ± SD of β-thalassemia intermedia (1629.48 ± 1235.33 ng/ml), with a p-value of 0.000. Patients with major β-thalassemia had a mean TSB level that was statistically significantly lower (1.32 ± 0.69 mg/dl) than the mean level of β-thalassemia intermedia (2.10 ± 0.86 mg/dl), with a p-value of 0.000. In the B-thalassemia major group, serum hepcidin did not exhibit a statistically significant association with serum ferritin (r=-0.04), while in the B-thalassemia intermedia group, serum ferritin exhibited a statistically significant moderate negative correlation with TSB (r=-0.38), p-value. 0.01.Conclusions:Ferritin levels may be useful in thalassemia syndrome diagnosis and prognosis determination